Unusual oximes with anti-inflammatory activities from Glycosmis craibii. (August 2021) - Wu, Shou-Yuan; Chen, Zi-Ming; Zhou, Zhong-Liu; Huang, Li-Ping; Huang, Guo-Ling; Zhou, Qi
Graphical abstract: Highlights: Two new and two known oximes were isolated from Glycosmis craibii . Compounds 1 −4 are unique plant natural products with an aldoxime functional group. Compounds 1 −4 exhibited anti-inflammatory activity in an IC50 range of 2.38-8.43 μ M. Abstract: Two new aldoximes A–B (1 −2 ), and two known analogues (3 −4 ), were identified from ethanolic extracts of Glycosmis craibii . The structures of new compounds 1 −2 were unambiguously elucidated based on spectroscopic methods. All isolated aldoximes were evaluated for their anti-inflammatory activity in vivo. Compounds 1 −4 displayed remarkable inhibitory effects against nitric oxide (NO) production stimulated by lipopolysaccharide in mouse macrophage RAW 264.7 cells with the IC50 values ranging from 2.38 ± 0.08–8.43 ± 0.21 μ M.